Coal Quality Control from Front to Stockpile at PT. Khatulistiwa Makmur Persada - Muhammad Fikri; Heri Prabowo (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
Khatulistiwa Makmur Persada is a company engaged in the coal mining industry. Meanwhile at PT. Khatulistiwa Makmur Persada, there are indications of a decrease in coal quality when coal is mined, this is due to a pool of water around the coal to be mined. This research was conducted using quantitative research methods. Quantitative research methods. By conducting tests on coal samples and interviewing workers for questionnaires. The results of the analysis of coal quality show changes when coal is transported to the stockpile from the mining front with a change in quality of 2.78% total moisture, 15.65 ash content, 1305.01 Kcal/kg calorific value. And the results of the analysis of changes in the quality of coal in the stockpile with the range determined by the company with a total moisture value of 1.36%, ash content of 7.46%, calorific value of 708.03 Kcal/kg. PT. Khatulistiwa Makmur Persada merupakan perusahaan yang bergerak di bidang industri pertambangan batubara. Sementara itu di PT. Khatulistiwa Makmur Persada, terdapat indikasi terjadinya penurunan kualitas batubara pada saat batubara ditambang, hal ini disebabkan adanya genangan air di sekitar batubara yang akan ditambang. Penelitian ini dilakukan dengan menggunakan metode penelitian kuantitatif. Metode penelitian kuantitatif. Dengan melakukan pengujian terhadap sampel batubara dan wawancara pekerja untuk kuisioner. Hasil analisis kualitas batubara menunjukkan perubahan pada saat batubara diangkut ke stockpile dari front penambangan dengan perubahan kualitas 2,78% total moisture, 15,65 ash content, 1305,01 Kcal/kg calorific value. Dan hasil analisis perubahan kualitas batubara di stockpile dengan range yang telah ditetapkan perusahaan dengan nilai total moisture 1,36%, ash content 7,46%, nilai kalori 708,03 Kcal/kg.